The 1st International Electronic Conference on Biosensors 2020
DOI: 10.3390/iecb2020-07063
|View full text |Cite
|
Sign up to set email alerts
|

Realization of Enhanced Evanescent Field Long Period Fiber Grating near Turn around Point for Label-Free Immunosensing

Abstract: A long-period fiber grating (LPFG) with maximum enhancement of evanescent field has been designed and fabricated, along with theoretical modeling, by working near the turn-around point (TAP) of the lowest order symmetric cladding mode (LP0.2 cladding mode). The LPFG was fabricated using a point-by-point inscription technique and it was characterized in terms of surrounding refractive index (SRI) within the range of 1.333 to 1.3335 using a thermostated flow-cell. This closed cell, made of poly(methyl methacryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…2021, 5, 48 2 of 7 mode, followed by self-assembled ssDNA probes [13]. Using a long-period fiber grating (LPFG) platform, Liu et al demonstrated the use of a LPFG coated with graphene oxide (GO) nanosheets using the changes in resonant intensity to measure different concentrations of hemoglobin adsorbed by the GO layer [14]; Chiavaioli et al reported a D-shaped single mode optical fiber (SMF) nanocoated with different metals for IgG/anti-IgG assays, reaching limit of detections (LOD) around to the femtomolar values [15]; and Dey et al presented a sensitivity-enhanced LPFG near the turning point by etching the fiber with hydrofluoric acid to detect anti-mouse IgG [16]. In a similar approach to this work, Liu et al demonstrated an LPFG-coated with silica nanoparticles modified with gold nanoparticles (AuNPs).…”
Section: Introductionmentioning
confidence: 99%
“…2021, 5, 48 2 of 7 mode, followed by self-assembled ssDNA probes [13]. Using a long-period fiber grating (LPFG) platform, Liu et al demonstrated the use of a LPFG coated with graphene oxide (GO) nanosheets using the changes in resonant intensity to measure different concentrations of hemoglobin adsorbed by the GO layer [14]; Chiavaioli et al reported a D-shaped single mode optical fiber (SMF) nanocoated with different metals for IgG/anti-IgG assays, reaching limit of detections (LOD) around to the femtomolar values [15]; and Dey et al presented a sensitivity-enhanced LPFG near the turning point by etching the fiber with hydrofluoric acid to detect anti-mouse IgG [16]. In a similar approach to this work, Liu et al demonstrated an LPFG-coated with silica nanoparticles modified with gold nanoparticles (AuNPs).…”
Section: Introductionmentioning
confidence: 99%